Crossing Rivers, Revisiting Trauma, and Contemplating the Geo: Thinking into the Anthropocenic. Issue 1 (2nd January 2017) - Westgate, Justin
Abstract : The irony of the Anthropocene—an idea grounded in earth sciences—is that it acts to unground some of the foundational ideas about the world. It asks us to reevaluate and rethink the human–nature binary, to inhabit a world less hospitable and malleable than we dared to believe. I explore this notion of groundlessness by returning to a personally traumatic event that literally swept me off my feet—crossing a river. I argue that the experience of such corporeal vulnerability can provide fertile ground for reorienting our own perception. Delving into such experiences may be used to provoke and expand thinking with a view to grappling with the implications of living within conditions of an Anthropocenic world.